Validation of an optimised microwave-assisted acid digestion method for trace and ultra-trace elements in indoor PM2.5 by ICP-MS analysis. Issue 1 (January 2023) - Camilleri, Renato; Stark, Christopher; Vella, Alfred J.; Harrison, Roy M.; Aquilina, Noel J.
Abstract: Three microwave-assisted digestion procedures, followed by analysis of digestates employing inductively coupled mass spectrometry (ICP-MS) were evaluated for use in the determination of elements at trace and ultra-trace levels in PM2.5 samples. Digestion procedure 1 used 2.5 mL HNO3 (65%) at 200 °C. Procedure 2, consisted of a two-stage digestion step at 200 °C with 2.5 mL HNO3 (65%) and 3 μL HF (48%) followed by 24 μL H3 BO3 (5%). A 10-fold increase in the amounts of HF and H3 BO3 was used for procedure 3. The addition of HF/H3 BO3 was carried out to aid the dissolution of silicate matrices and refractory compounds. The digestions were carried out using PTFE ultra-trace inserts which increased the sample throughput threefold. The addition of small quantities of HF resulted in the effective solubilisation of Na, Mg, Al, K, Ca, Ti, V, Cr, Mn, Fe, Ni, Cu, Zn, As, Sr, Cd, Sb and Pb. The optimal method using HNO3 /HF/H3 BO3 digestion as in procedure 3 showed recovery efficiency greater than 70% for all elements. The validated method was applied to quantify the elemental content of indoor and outdoor PM2.5 (with samples <0.5 mg) at an urban background site in Malta.